A Label for Opening of the Mouth Implements from the Burial of Senneferi (TT99) and Remarks on the Ritual - Bohleke, Briant; Strudwick, Nigel (Études et Travaux, 2017)
In 2009, Nigel Strudwick published a paper drawing attention to a number of objects found in TT99 which seem to have been used in the Opening of the Mouth ritual. In 2015 an hieratic label from the same burial was identified as possibly belonging to a bag or box in which these items were kept. This paper presents a full edition of the label, and offers further comments on the context where the objects were found, and also indicates lines of research for further study of the Opening of the Mouth ritual.